Роль опорного закладу освіти сільської територіальної громади в системі забезпечення надання корекційно-розвиткових послуг для учнів з порушеннями мовлення - Мицик, Ганна Михайлівна (Кропивницький : РВВ ЦДПУ ім. В. Винниченка, 2022)
У статті здійснено дослідження стану функціонування опорних закладів освіти у сільській місцевості; звернуто увагу на особливості організації інклюзивного навчання учнів з особливими освітніми потребами в таких закладах; виявлені проблеми, що ускладнюють надання логопедичних послуг учням з порушеннями мовлення вчителем-логопедом в опорних закладах освіти; запропоновані шляхи їх розв’язання.
In the context of bridging the gap between the quality of education in urban and rural areas in Ukraine, in the framework of the educational reform of general secondary education, a new educational institution by organization and structure form which is a basic educational institution was proposed. With the expansion of the practice of inclusive education of children with special educational needs in general secondary education institutions, it is appropriate to talk about bridging this gap and for providing correctional and developmental services to such children as part of correctional and developmental services for children with speech disorders. The assessment of the possibilities of the basic educational institutions in their readiness to provide correctional and developmental services to children with special educational needs showed that among pedagogical positions of the basic educational institutions and their branches mostly need speech therapists. Taking into account the features of the rural environment the necessity of increasing the access to correctional and developmental services for children with speech disorders living in rural areas is proved. First of all, it is necessary in rural settlements which remote from educational institutions. It exacts from a speech therapist the other way of building his work in this direction. As an alternative, the possibility of organizing such work at a distance using distance learning technologies is considered. Despite the positive changes in the implementation of inclusive education in Ukraine, it is noted that the level of logistics of the basic educational institution in rural area doesn’t allow to speech therapist using their potential in organizing correctional and developmental work for children with speech disorders in full extent. The opinion of necessity to solve the staffing issue, improve the logistics and educational provision of the basic educational institutions, which would allow to a speech therapist to organize and conduct correctional and developmental work properly within the single educational space was expressed.
Keywords: сільська місцевість; опорний заклад освіти; філія; інклюзивне навчання; корекційно-розвиткова допомога; діти з порушеннями мовлення; вчитель-логопед